RUPTURED RUDIMENTARY HORN PREGNANCY OF UNICORNUATE UTERUS AT HIWOT FANA SPECIALIZED HOSPITAL, HARAR, ETHIOPIA: A CASE REPORT - Belay, Lemi; Gure, Tadesse; Teshome, Abel; Asrat, Matias (Ethiopian Journal of Reproductive Health, 2019)
ABSTRACT Unicornuate uterus with rudimentary horn occurs due to failure of complete development of one of the mullerian ducts and incomplete fusion with the contra lateral side. Pregnancy in the non-communicating rudimentary horn is extremely rare and usually terminates in rupture during first or second trimester of pregnancy. Pregnancy occurs via trans peritoneal migration of sperm or zygote. Variable thicknesses of rudimentary horn musculature, poor dispensability of myometrium lead to rupture. This complication is usually seen in 2nd trimester resulting in shock and hemoperitoneum. Diagnosis of rudimentary horn pregnancy is difficult and can be missed in ultrasound. Diagnosis of rudimentary horn pregnancy is difficult and can be missed by ultrasound. We report a case of ruptured rudimentary horn pregnancy at 17 weeks of gestation. KEYWORDS: Rudimentary horn, Unicornuate uterus, Hemoperitoneum, Rupture. (Ethiopian Journal of Reproductive Health; 2019; 11;2:56-60)